Acute renal failure with polyarteritis nodosa and multiple myeloma. Issue 715 (May 1985) - Williams, A. J.; Newland, A. C.; Marsh, F. P.
Abstract : A patient who presented with acute renal failure due to renal cortical necrosis is described. Renal biopsy showed cortical infarction and angiography demonstrated aneurysms in the renal, splenic and hepatic circulations. Concurrently he was found to have an IgA kappa paraprotein with bone marrow changes diagnostic of multiple myeloma. He was treated with haemodialysis, immunosuppressive drugs and plasma exchange but died 3 months after presentation.